2011
DOI: 10.1179/2045772311y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

Spinal tuberculosis: A review

Abstract: Spinal tuberculosis is a destructive form of tuberculosis. It accounts for approximately half of all cases of musculoskeletal tuberculosis. Spinal tuberculosis is more common in children and young adults. The incidence of spinal tuberculosis is increasing in developed nations. Genetic susceptibility to spinal tuberculosis has recently been demonstrated. Characteristically, there is destruction of the intervertebral disk space and the adjacent vertebral bodies, collapse of the spinal elements, and anterior wedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
660
3
74

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 617 publications
(796 citation statements)
references
References 93 publications
16
660
3
74
Order By: Relevance
“…From there, the infection tracks in a typical subligamentous fashion beneath the anterior and posterior longitudinal ligaments to the neighboring vertebrae, resulting in contiguous vertebral involvement. Progressive vertebral destruction leads to multiple consecutive vertebral collapses, eventually resulting in kyphosis and gibbus formation [2,3]. This typical imaging appearance of TB spondylitis was present in this patient.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…From there, the infection tracks in a typical subligamentous fashion beneath the anterior and posterior longitudinal ligaments to the neighboring vertebrae, resulting in contiguous vertebral involvement. Progressive vertebral destruction leads to multiple consecutive vertebral collapses, eventually resulting in kyphosis and gibbus formation [2,3]. This typical imaging appearance of TB spondylitis was present in this patient.…”
Section: Discussionmentioning
confidence: 57%
“…TB is a prevalent granulomatous infection. Bony involvement accounts for approximately 5 % of extrapulmonary TB, of which vertebral involvement accounts for approximately 50 % of them [2,3]. Both TB and ALCL can involve different organs and are known to be mimickers of disease with a few reports of the two entities masquerading as the other, particularly in the form of vertebral involvement [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poncet's arthritis, [4] TB arthritis, [5] peripheral septic arthritis, [6] TB spondylodiscitis and SI are some forms of presentation of extrapulmonary tuberculosis. [7][8][9][10] Even without any pathognomonic radiologic sign of TB SI, nuclear resonance showing subchondral bone marrow edema and irregularity of articular surface on an asymmetric distribution confirms unilateral SI. [11,12] Asymmetric SI without any other findings suggestive of spondiloarthropathy should be promptly investigated for infectious disease.…”
Section: Discussionmentioning
confidence: 94%
“…Most patients with spinal tuberculosis respond to medical treatment. 3 Antituberculosis treatment protocols used for treatment of spinal tuberculosis vary from 6 to 18 months. British Medical Research Council studies have indicated that thoracolumbar spinal tuberculosis needs be treated with a combination antituberculosis treatment regimen for 6-9 months.…”
Section: Introductionmentioning
confidence: 99%